2016
DOI: 10.21206/rbas.v6i3.351
|View full text |Cite
|
Sign up to set email alerts
|

Resíduos Compostados Como Substrato Para Produção De Petunia X Hybrida

Abstract: A transformação de resíduo em tecnologia deve ser uma prioridade atual no setor agrícola, diminuindo o descarte inadequado e recuperando parte daquilo que é produzido e que pode retornar como nutriente as plantas. O presente trabalho teve por objetivo buscar uma solução viável de uso de resíduos vegetais como a poda de grama, o bagaço de cana e o esterco bovino como substrato para o cultivo de plantas. Os resíduos utilizados foram compostados, e utilizados como substratos para a produção de petúnia, uma espéci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The use of substrates with slightly higher carbon/nitrogen ratio favors the decomposition and mineralization of a good part of the residues, but still keeps a small part to be decomposed, favoring the continuous release of nutrients throughout the plant cycle (ZANELLO; CARDOSO, 2016). Similar results were obtained by Ferreira and Rodrigues (2015), who found that substrates composed of bovine manure resulted in papaya seedlings with greater phytomass, independent of the addition of mineral fertilizers.…”
Section: Resultsmentioning
confidence: 52%
“…The use of substrates with slightly higher carbon/nitrogen ratio favors the decomposition and mineralization of a good part of the residues, but still keeps a small part to be decomposed, favoring the continuous release of nutrients throughout the plant cycle (ZANELLO; CARDOSO, 2016). Similar results were obtained by Ferreira and Rodrigues (2015), who found that substrates composed of bovine manure resulted in papaya seedlings with greater phytomass, independent of the addition of mineral fertilizers.…”
Section: Resultsmentioning
confidence: 52%
“…Thus, the addition of the compost to the substrate contributed to decrease the acidity and, consequently, the availability of Al and to increase the availability of some nutrients in the environment. Zanello & Cardoso (2016) also observed limited development of petunias in pots using the same commercial substrate, whereas the use of the compost containing mowed grass and cattle manure as cultivation substrate proved to be more adequate.…”
Section: Resultsmentioning
confidence: 94%
“…In studies using food residue compost in lettuce cultivation, Freitas et al (2018) observed higher shoot fresh mass (14 g/plant) using 100% of compost, when compared with different mixtures of soil and compost, showing that this type of residue has potential to be used in composting. A compost of mowed grass with cattle manure showed high potential as substrate for petunia cultivation, showing much superior performance (42 g/plant of fresh mass) when compared with commercial substrates that are used for this same purpose, such as ground pine bark (21 g/plant fresh mass) and coconut powder, being the good results attributed to the higher levels of macro and micronutrients in the compost (Zanello & Cardoso, 2016). Among some advantages of using organic fertilizer are the higher ascorbic acid concentration in plant leaves (26 to 44%) and the lower nitrate content in plant leaves in this system (66.7 mg/kg) than in those with mineral fertilization (113.6 mg/kg) and hydroponics (278.4 mg/kg).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations